Applying ecological systems theory to juvenile legal system interventions outcomes research: a measurement framework - Sheerin, Kaitlin M.; Brodell, Regina; Huey, Stanley J.; Kemp, Kathleen A. (Frontiers in Psychology, 2023)
Intervention research and development for youth in the juvenile legal system (JLS) has often focused on recidivism as the primary outcome of interest. Although recidivism is an important outcome, it is ultimately a downstream marker of success and is affected by changes in other domains of youths’ lives (e.g., family and peer relations, neighborhood safety, local and state-level policies). Thus, the present manuscript proposes the application of ecological systems theory to selecting outcomes to assess intervention effects in JLS intervention research to better capture proximal and distal influences on youth behavior. To that end, we first provide an overview of the strengths and limitations of using recidivism as an outcome measure. Next, the current application of social ecology theory to existing research on both risk and protective factors of JLS involvement is discussed, as well as existing work on assessing social-ecological domains within intervention studies. Then, a measurement framework is introduced for selecting pertinent domains of youths’ social ecologies to assess as intervention outcomes, moderators, and mediators. To facilitate this, we provide examples of concrete constructs and measures that researchers may select. We conclude with potential new avenues of research to which our proposed framework could lead, as well as potential limitations of implementing our framework.